Zurvan: the concept of time in Zoroastrianism and its impact on religion and philosophy - Katerina Gololobova (Cхід, 2017)
The concept of time is an integral part of any religious and philosophical system. It creates a universal cognitive strategy: seeing the world in its change and development, finding temporary relationships and order in everything. In Iranian mythology, where the cult of time was highly developed, time was personified by the higher deity Zurvan, who initially was imagined as an endless time, eternity (Zurvan Akaran), existing at the beginning of the universe, and then, in the latter part of the "Avesta" takes an image of the final, natural, world time (Zurvan Darhahvadata), who forecasts not only its beginning, but the end, death.